Long-term outcomes of Graves' disease in children and adolescents receiving antithyroid drugs - Jung Gi Rho; Change Dae Kum; Young Jun Seo; Young Suk Shim; Hae Sang Lee; Jin Soon Hwang (Korean Society of Pediatric Endocrinology, 2021)
Purpose Antithyroid drugs (ATDs) are primarily used as an initial treatment in pediatric patients with Graves' disease (GD). We aimed to investigate the long-term outcomes in pediatric GD patients receiving ATDs. Methods Retrospective data from a single center were collected from April 2003 to July 2020. A total of 98 children and adolescents aged 2-16 years diagnosed with GD and receiving ATDs was enrolled. We investigated the factors correlated with remission by comparing children who achieved remission after 5 years and those with persistent disease. Results The study included 76 girls (77.6%) and 22 boys (22.4%). During the 5-year follow-up period, 18 children (18.3%) maintained remission, ATDs could not be discontinued in 74 patients (75.5%), and relapse occurred in 6 patients (6.2%). The remission group had significantly lower thyroid-stimulating hormone-binding inhibitory immunoglobulin (TBII) level at diagnosis (P=0.002) and 3 months (P=0.002), 1 year (P=0.002), 2 years (P≤0.001), 3 years (P≤0.001), 4 years (P≤0.001), and 5 years (P≤0.001) after ATD treatment than did the nonremission group. The remission group also had a shorter time for TBII normalization after ATD treatment (P≤0.001). Multiple logistic regression analysis showed that the time to TBII normalization (cutoff time=2.35 years) was related to GD remission (odds ratio, 0.596; 95% confidence interval, 0.374-0.951). Conclusions TBII level and time to TBII normalization after ATD treatment can be used to predict remission in pediatric GD patients.